Penentuan Tarif Kamar pada Hotel Y Surabaya dengan Metode Activity Based Costing - Sukamto, Yunike Helena; Febriyanti, Galuh Artika (Jurnal Akuntansi dan Pajak, 2024)
Activity Based Costing System is an accounting method that can be used to find the total cost of activities needed to make a product. The cctivity based costing method assigns costs to each activity that goes into production, such as workers testing a product. Activity Based Costing System aims to identify activities that generate cost currency. The primary focus is on the activities performed on a particular product during its production. Thus, activity is the focal point in costing. In an activity based costing method, overhead costs are assigned to cost centers or units based on the number of activities performed in production. This tudy aims to analyze the determination of hotel room rates using the activity based costing method at Y hotel Surabaya. This type of research is qualitative research to obtain descriptive data. The result obtained are the hotel room rates carried out by Y hotel Surabaya have a greater value compared to hotel room rates using the activity based costing method.